Magnesium hydroxide-incorporated PLGA composite attenuates inflammation and promotes BMP2-induced bone formation in spinal fusion. (October 2020) - Bedair, Tarek M.; Lee, Chang Kyu; Kim, Da-Seul; Baek, Seung-Woon; Bedair, Hanan M.; Joshi, Hari Prasad; Choi, Un Yong; Park, Keun-Hong; Park, Wooram; Han, InBo; Han, Dong Keun
Spinal fusion has become a common surgical technique to join two or more vertebrae to stabilize a damaged spine; however, the rate of pseudarthrosis (failure of fusion) is still high. To minimize pseudarthrosis, bone morphogenetic protein-2 (BMP2) has been approved for use in humans. In this study, we developed a poly(lactide-co-glycolide) (PLGA) composite incorporated with magnesium hydroxide (MH) nanoparticles for the delivery of BMP2. This study aimed to evaluate the effects of released BMP2 from BMP2-immobilized PLGA/MH composite scaffold in an in vitro test and an in vivo mice spinal fusion model. The PLGA/MH composite films were fabricated via solvent casting technique. The surface of the PLGA/MH composite scaffold was modified with polydopamine (PDA) to effectively immobilize BMP2 on the PLGA/MH composite scaffold. Analyzes of the scaffold revealed that using PLGA/MH-PDA improved hydrophilicity, degradation performance, neutralization effects, and increased BMP2 loading efficiency. In addition, releasing BMP2 from the PLGA/MH scaffold significantly promoted the proliferation and osteogenic differentiation of MC3T3-E1 cells. Furthermore, the pH neutralization effect significantly increased in MC3T3-E1 cells cultured on the BMP2-immobilized PLGA/MH scaffold. In our animal study, the PLGA/MH scaffold as a BMP2 carrier attenuates inflammatory responses and promotes BMP2-induced bone formation in posterolateral spinal fusion model. These results collectively demonstrate that the BMP2-immobilized PLGA/MH scaffold offers great potential in effectively inducing bone formation in spinal fusion surgery.